Pengembangan Media Komik Digital pada Materi Siklus Air untuk Meningkatkan Hasil Belajar Siswa Kelas V SD Negeri 5 Pontianak Timur - Haryanto, Henzi; Kartono, Kartono; Pranata, Rio (FONDATIA, 2023)
The purpose of this study was to develop digital comic learning media on water cycle material as an effort to improve student learning outcomes. This research is a Research and Development (R&D) study by applying the ADDIE research stages. Data collection in this study was carried out through questionnaires, interviews, tests, validation, and questionnaire sheets. The subjects in this study involved 27 students for two months, starting from February-March 2023. The research findings show that digital comic products have gone through the stages of making, validation, and limited trials. The results of the material expert validation received a score of 3.30 with the label "feasible" while the media expert validation received a score of 4 with the label "very feasible". The pre-test results obtained a score of 62.03 and the post-test score increased and obtained a score of 72.59. The level of practicality of the use and presentation of digital comics learning water cycle material is 3.52 from students and 30 from class teachers with "very feasible" criteria. Based on the results of the study, it can be concluded that the use of digital comic learning media is effective in improving student learning outcomes.